2018
DOI: 10.3389/fpls.2018.01422
|View full text |Cite
|
Sign up to set email alerts
|

QTL Mapping of Six Spike and Stem Traits in Hybrid Population of Agropyron Gaertn. in Multiple Environments

Abstract: Most Agropyron Gaertn. species are excellent sources of forage. The derivative lines of wheat-Agropyron cristatum show elite agronomic traits, and some are valuable for wheat breeding. The species of Agropyron Gaertn. was mainly recognized by the spike morphology in traditional taxon. Six traits, including spike length (SL), ear stem length (ESL), the second internodes length (SIL), spikelet number per spike (SNS), floret number per spikelet (FNS), and grain number per spikelet (GNS), are vital to morphology s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
11
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 12 publications
(13 citation statements)
references
References 39 publications
2
11
0
Order By: Relevance
“…In the present study, by assessing two spikelet number-related traits TSN and FSN in a DH population among five environments, we found that TSN and FSN were significantly and positively correlated with GNS (Table 2) with a high heritability (0.85 for TSN and 0.82 for FSN) ( Table 1). The results were consistent with previous knowledge (Che et al, 2018;Würschum et al, 2018;Zhang et al, 2019) that they are environmentally stable yield components and mainly determined by genetic factors. Therefore, increasing spikelet number could be considered as an effective strategy for increasing GNS and hence the grain yield.…”
Section: Discussionsupporting
confidence: 92%
“…In the present study, by assessing two spikelet number-related traits TSN and FSN in a DH population among five environments, we found that TSN and FSN were significantly and positively correlated with GNS (Table 2) with a high heritability (0.85 for TSN and 0.82 for FSN) ( Table 1). The results were consistent with previous knowledge (Che et al, 2018;Würschum et al, 2018;Zhang et al, 2019) that they are environmentally stable yield components and mainly determined by genetic factors. Therefore, increasing spikelet number could be considered as an effective strategy for increasing GNS and hence the grain yield.…”
Section: Discussionsupporting
confidence: 92%
“…Tillering ramets from individual F 1 population obtained by crossing between A. mongolicum Z2098 (female) and A. cristatum Z1842 (male) and parents, a total of 115 individuals (including two parents), were transplanted to two different locations, that is Changli campus plots and the farm of Hebei Normal University of Science and Technology, in April 2013 (Che et al, 2018). Conventional field management practices were used at farm study sites.…”
Section: Methodsmentioning
confidence: 99%
“…When the p value of the marker was less than the threshold, it was considered that there was a trait‐related QTL at the marker. A QTL with an LOD value >2.5 and a contribution rate of >10% detected in different environments was defined as a major QTL, and the QTL detected in at least three different environments was regarded as a stable QTL (Che et al, 2018; Fan et al, 2015; Wang, 2009). The QTL was named according to the method described by Mccouch et al (1997).…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…constructed using a CP population that contains 1,023 markers on seven linkage groups, with a total of 907.8 cm and an average distance of 1.5 cm between adjacent loci (Zhang et al, 2015). Based on this map, the major and stable QTL for plant height (PH; Che et al, 2020) and QTL for other characteristics of the spike (Che et al, 2018) in A. Gaertn. have been detected.…”
Section: Introductionmentioning
confidence: 99%